21st Century Management Leadership and Innovation in the Thought Economy - Lindgren, M. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2012)
Explores the changing business landscape of the 21st century and what it means for organizations. The author presents a new model for how to think about and handle the complex world of business from a managerial and innovative perspective with tips and tools for motivating and engaging your organization, clients and customers.